Wall cakes - Cruz, Yvette Kryzel C.; Sta Ana, Mary Catherine; Feleo, Roberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
This thesis is concerned with appropriating methods and materials of cake-making into the practice of painting and with the presentation of multi-sensorial cues attributed to eating cakes in an attempt to link the visual and the gustatory experience. Strategies employed were to create paintings using pastry materials, to provide a multi-sensorial experience using food presentation and painting, and to identify the similarities in the creation of paintings and cakes to resolve the presentation of both in a gallery setting.

The work bases its assumptions on the mind's ability to synthesize information from multiple sensory systems to influence perception, decisions, and behavior. The work consists of three components: an acrylic painting, an identical edible cake work, and a shelf on which will be objects used for eating. It relies on the viewer's experience of cakes to relate the visual and the gustatory senses. The work explores the expansion of the definition of painting and relates it with simulacra. Through the use of visual resemblance between two works, and through the provision of eating tools, the thesis offers work that may be expressly experienced through taste, touch, and smell.

This project serves as a way to look into the acts of painting and of interacting with work through methods that incorporate materials and methods of baking into painting.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 22-23
Keywords: Food as art; Simulacra; Multi sensory system